A Framework for Understanding the Nature of Questions Asked by Audience Participants at Science Cafés - Nesseth, Nina M.; Henson, Amy M.; Barriault, Chantal L. (Frontiers in Education, 2021)
Science Cafés are events designed as public engagement tools that create the opportunity for open dialogue between members of the general public and experts on the issue being discussed at the event. This study explores the nature of questions being asked by audience participants during discussion sessions of Science Café events. It was conducted by coding audio recordings of audience participant engagements at 41 Science Café events held between 2010 and 2019. The result of this analysis produced a novel taxonomic framework to describe audience participant behaviors in terms of their learning goals. This framework was evaluated by applying it to samples of Science Café question data selected by Science Café topic theme. Comparisons between question-asking behaviors for specific Science Café topics and overall trends in question-asking behaviors for all Science Cafés revealed significant changes in audience participant learning goals when asking questions at Science Cafés centered on different topic types. Implications for understanding Science Café audiences and potential developments for Science Café events as public science engagement tools are discussed.